2013
DOI: 10.1128/iai.01096-12
|View full text |Cite
|
Sign up to set email alerts
|

Quorum-Sensing Systems LuxS/Autoinducer 2 and Com Regulate Streptococcus pneumoniae Biofilms in a Bioreactor with Living Cultures of Human Respiratory Cells

Abstract: dStreptococcus pneumoniae forms organized biofilms in the human upper respiratory tract that may play an essential role in both persistence and acute respiratory infection. However, the production and regulation of biofilms on human cells is not yet fully understood. In this work, we developed a bioreactor with living cultures of human respiratory epithelial cells (HREC) and a continuous flow of nutrients, mimicking the microenvironment of the human respiratory epithelium, to study the production and regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 62 publications
1
100
0
Order By: Relevance
“…Where shown, error bars indicate the standard errors of the mean calculated using data from three independent experiments. the cbp gene, encoding C. perfringens beta toxin (61), is maximally expressed in planktonic cultures during the early-mid-log phase of growth (60). In comparison to planktonic cultures, the population of biofilm bacteria 4 h postinoculation had downregulated transcription of the cbp gene (ϳ4-fold decrease) but mRNA levels of cpa and pfoA remained similarly expressed (Fig.…”
Section: Figmentioning
confidence: 96%
See 1 more Smart Citation
“…Where shown, error bars indicate the standard errors of the mean calculated using data from three independent experiments. the cbp gene, encoding C. perfringens beta toxin (61), is maximally expressed in planktonic cultures during the early-mid-log phase of growth (60). In comparison to planktonic cultures, the population of biofilm bacteria 4 h postinoculation had downregulated transcription of the cbp gene (ϳ4-fold decrease) but mRNA levels of cpa and pfoA remained similarly expressed (Fig.…”
Section: Figmentioning
confidence: 96%
“…perfringens releases eDNA into the culture medium. The biofilm matrix of other pathogens, such as Streptococcus pneumoniae (61,62) or Enterococcus faecalis (63), is partially composed of DNA that has been excreted into the medium (i.e., eDNA). It has been recently reported that eDNA is present in the C. perfringens biofilm matrix (49,50).…”
Section: Production Of C Perfringens Biofilms Is Regulated By Enviromentioning
confidence: 99%
“…Controlling pneumococcal colonization may be a way to reduce the burden of disease, and so biofilm research has been a focus of basic science studies in my laboratory. We developed a life-like model that simulates the human upper and lower airways to investigate production of colonizing biofilms 8 . The last few years, we have learned that pneumococcal biofilms are controlled by quorum sensing, small molecules that activates other mechanisms of virulence 9 , including a potent toxin known as pneumolysin or Ply 10 .…”
Section: Nasopharyngeal Colonizationmentioning
confidence: 99%
“…Biofilm formation was performed on immobilized A549 cells as previously described (23). Briefly, cells were grown until confluent in 12-well polystyrene plates and immobilized by fixation with 2% paraformaldehyde (Sigma).…”
Section: Ethicsmentioning
confidence: 99%